2020
DOI: 10.1071/en19182
|View full text |Cite
|
Sign up to set email alerts
|

Identification of new hardy ferns that preferentially accumulate light rare earth elements: a conserved trait within fern species

Abstract: Environmental contextRare earth elements (REEs) are strategic metals and emerging contaminants for which plant-based remediation measures are needed. We screened a collection of hardy ferns and identified new accumulator species that preferentially transferred light REEs to their fronds. This study is an important step towards understanding the mechanisms of REE accumulation in plants. AbstractRare earth elements (REEs) include the lanthanides plus yttrium and scandium, and can be split according to their atom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 55 publications
2
12
0
Order By: Relevance
“…For instance, plants that accumulate REEs display specific enrichment of either LREEs or HREEs (Grosjean et al, 2020(Grosjean et al, , 2019. Taken together, these few available studies support the need to elucidate the cellular and molecular mechanisms involved in the response to REEs, similar to work performed on the specific REE yttrium (Grosjean et al, 2018).…”
Section: Introductionmentioning
confidence: 80%
“…For instance, plants that accumulate REEs display specific enrichment of either LREEs or HREEs (Grosjean et al, 2020(Grosjean et al, , 2019. Taken together, these few available studies support the need to elucidate the cellular and molecular mechanisms involved in the response to REEs, similar to work performed on the specific REE yttrium (Grosjean et al, 2018).…”
Section: Introductionmentioning
confidence: 80%
“…RE mobilization is positively correlated with that of Fe and Mn (Cao et al, 2001). Due to their higher mobility in soils, LRE are more easily absorbed and accumulated by plants than heavy RE since the latter form much more stable complexes in soil solution (Brioschi et al, 2013;Grosjean et al, 2020). Indeed, roots preferentially absorb free ions rather than dissolved complexes (Brioschi et al, 2013).…”
Section: Speciation Of Rare Earths In Different Matricesmentioning
confidence: 99%
“…A recent study identified new accumulating species RE using a screening method for ferns grown on RE contaminated substrate. Three species reached more than 200 mg/kg: Onoclea sensibilis, Athyrium othophorum and Athyrium filix-femina (Grosjean et al, 2020).…”
Section: The Use Of Hyper-accumulative Plants In the Context Of Phytominingmentioning
confidence: 99%
“…In addition to their different toxicity levels (HREEs > LREEs ( Tyler, 2004 ; Gonzalez et al, 2014 ; Goecke et al, 2017 )), only a few studies revealed the specific modes of action of these two REE groups with a single multi-scale analysis directly comparing the differential effect of two Ln ( Grosjean et al, 2021 ). As such, specific accumulation of LREEs has been reported in ferns ( Grosjean et al, 2020 ), while angiosperms preferentially translocate HREEs in their aboveground tissues ( Liu et al, 2018 ; Grosjean et al, 2019 ), thereby suggesting different transport systems between LREEs and HREEs. Molecular evidence also supports this hypothesis in S accharomyces cerevisiae , in which disruption of the Ca channel Cch1p/Mid1p restricts La but not Gd uptake ( Ene et al, 2015 ).…”
Section: Introductionmentioning
confidence: 97%